Development of IIUM circular planform unmanned aerial vehicle (IIUM-CPUAV) - Omar, Ashraf Ali; Abdullah, Nur Azam; Simat @ Mohd Akhir, Ahmad Zaahin (2012)
In this work, the first IIUM circular planform unmanned Aerial vehicle (IIUM-CPUAV) model, also know as geobat flying saucer was successfully designed, built and tested by the team from the Department of Mechanical Engineering, IIUM. The designing process started with gathering historical data and performing the conceptual design calculations. The maximum diameter and weight of IIUM-CPUAV are 1 m and 900 grams, respectively.Foam was the main material used to construct the IIUM-CPUAV. Flight tests were conducted successfully and IIUM-CPUAV was found to be stable. Based on the flight tests results, design modifications were carried out on the prototype to improve the stability and the performance. The final configuration of the IIUM-CPUAV was successfully tested.